Modelling the calibration/cooling stage of complex thermoplastic profiles - Ribau, A. M. (2013)
Thermoplastics have very low thermal diffusivity, which is advantageous for some applications but turn difficult their processing. In fact, in continuous processes, such as extrusion, it can limit the production rate, which is dependent on the installed cooling capability of the extrusion line, originates the development of considerable thermal gradients during the cooling stage and, consequently, the development of stresses that can be frozen in the product (generally referred as residual thermal stresses) that will affect negatively its mechanical performance in use. Therefore, the conditions in which the cooling stage takes place not only determine the production rate, but also the final properties of extruded products. Due to the large number of parameters influencing the cooling stage, the optimization of this stage requires the use of proper modeling codes. The work here presented is intended to improve the scope of application of an existing 3D non-isothermal multi-domain numerical code based on the finite volume method (FVM), through the implementation of unstructured meshes enabling, therefore, to predict the evolution of the thermal field during the cooling stage of the extrusion of complex profiles.